Continuing the (un)finished: A Dialogue with the Painting (EAAE Annual Conference Proceedings, 2025)
Contemporary architectural education often prioritizes originality over continuity, even in adaptive reuse. This mindset reduces layered spaces into geometric abstractions – mere volumes awaiting intervention, rather than acknowledging them as lived spaces with their own identity, memory, and atmosphere. This paper challenges the tendency among students to view existing buildings as empty shells, advocating for a pedagogical approach rooted in sensitivity and slowness.Drawing on Pérez de Arce’s idea that the built environment evolves over time through the gradual layering of elements. This incremental process confirms and reinforces a space, imbuing it with collective experiences, and socio-cultural and spatial values.(1) Erasing this accumulation means losing something meaningful and qualitative. The question arises: what does it truly mean to continue a lived space, and how can it be taught?This contribution discusses an exercise of the research seminar Genius Loci, coordinated by Koenraad van Cleem-Poel, in which students engage in a nuanced dialogue between theory and practice through the in-depth study of a painting. By interpreting an artwork’s visual, emotional, and symbolic layers, students cultivate a sensitivity that informs their own translations – soft interventions and personal interpretations that maintain a respectful dialogue with the original.Through qualitative analysis of student projects, the paper demonstrates an approach that fosters sensitivity towards existing conditions and promotes a design language rooted in continuation rather than demolition. The research advocates for an open-ended approach, refined by an attitude of sensitivity towards the lived space and its thoughtful reuse. In this process of reflection and redefinition, the painting serves as a metaphor for the lived space, encouraging interaction to continue rather than to erase.1. Pérez de Arce, Rodrigo. “Urban Transformations & the Architecture of Additions.” Architectural Design 48, no. 4 (1978): 237–266.